2015
DOI: 10.1007/jhep02(2015)112
|View full text |Cite
|
Sign up to set email alerts
|

Correlation functions in ω-deformed N = 6 $$ \mathcal{N}=6 $$ supergravity

Abstract: Gauged N = 8 supergravity in four dimensions is now known to admit a deformation characterized by a real parameter ω lying in the interval 0 ≤ ω ≤ π/8. We analyse the fluctuations about its anti-de Sitter vacuum, and show that the full N = 8 supersymmetry can be maintained by the boundary conditions only for ω = 0. For nonvanishing ω, and requiring that there be no propagating spin s > 1 fields on the boundary, we show that N = 3 is the maximum degree of supersymmetry that can be preserved by the boundary cond… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 44 publications
3
14
0
Order By: Relevance
“…These results are consistent with the detailed AdS/CFT analysis of []. There it was shown that the standard boundary conditions for fluctuations in AdS4 of the generic prefixitalicSO(8) gaugings are only supersymmetric for the standard ω=0 case.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These results are consistent with the detailed AdS/CFT analysis of []. There it was shown that the standard boundary conditions for fluctuations in AdS4 of the generic prefixitalicSO(8) gaugings are only supersymmetric for the standard ω=0 case.…”
Section: Discussionsupporting
confidence: 89%
“…The de Wit–Nicolai theory famously arises as a consistent truncation of eleven‐dimensional supergravity on a round seven‐sphere . A natural question is whether all the theories in the family can be realised in higher‐dimensional supergravity, or, more generally, as string or M theory backgrounds, a possibility that has been investigated by a number of authors …”
Section: Introductionmentioning
confidence: 99%
“…As a consistency check, if we write 4) then in order that S ′ , S ′ and P ′ , P ′ should be dual to ∆ = 1 and ∆ = 2 primary operators respectively, the boundary conditions 5) JHEP08 (2015)122 should preserve the N = 1 supersymmetry of ω-deformed supergravity in the bulk. In terms of the original fields, the above boundary conditions amount to These are consistent with the N = 1 boundary conditions given in [42] for the ω-deformed SO (8) gauged N = 8 supergravity.…”
Section: Jhep08(2015)122supporting
confidence: 73%
“…18 Similar phenomenon was discovered in the ω-deformed N = 6 supergravity [38]. There due to nonlinear effects, the mixing angle takes discreet values.…”
Section: Supersymmetric Boundary Conditionsmentioning
confidence: 64%